A Novel Low Cost Fractal Antenna Structure for ISM and WiMAX Applications - Driss El Nabaoui; Abdelali Tajmouati; Jamal Zbitou; Ahmed Errkik; Larbi Elabdellaoui; Mohamed Latrach (Universitas Ahmad Dahlan, 2018)
Different fractal structures have been widely used in many antennas designs for various applications. A fractal antenna is used for miniaturization and multiband operation. This paper presents a design of a dual-band fractal antenna fed by coplanar waveguide (CPW) transmission line. The proposed antenna is designed and fabricated on an FR4 substrate with a volume of 70x60x1.6mm3, resonates at 2.42-2.62GHz and 3.40-3.65GHz with a return loss less than -10dB. The design and simulation process is carried out by using CST-MW studio electromagnetic solver. Simulation results show that the resulting antenna exhibits an interesting dual frequency resonant behavior making it suitable for dual band communication systems including the ISM and WiMAX applications. Concerning the fabrication and measurement of the final prototype of this antenna, a good agreement is found between simulation and measurement results for both frequency bands.